Examining students’ Self-Assessment of Digital Argumentation (SADA) in e-biology class: A Rasch analysis - Marheny Lukitasari; Jeffry Handika; Wasilatul Murtafiah; Agita Risma Nurhikmawati (University of Muhammadiyah Malang, 2020)
Self-Assessment of Digital Argumentation (SADA) is considerable instrument to assess students’ digital argumentation (DA) in e-learning model. The research objectives were: (1) to investigate how SADA can be used as an instrument for assessing students’ DA; and (2) to access students’ DA through SADA in e-Biology class. The study population was 132 students of Biology Education Department of UNIPMA in which the 64 students as the samples were taken purposively. The instrument used was the SADA questionnaire. The data were analyzed using Rasch model. The statistical summary showed that the interaction between respondents and items was very good (Cronbach alpha was 0.95 > 0.8). Meanwhile, the person reliability (0.92) and item reliability (0.75) were categorized as were categorized as